The role of environmental factors in childhood asthma - Räyhäntausta, Nora (My University, 2023)
Background: Asthma is a common chronic respiratory disease affecting people worldwide. The prevalence, incidence, mortality and economic burden of asthma have increased since 1960 in developed countries, especially among children. Although higher asthma-related mortality rates occur in low- and middle-income countries. Childhood-onset asthma is typically allergic and accompanied by other allergic diseases such as atopic dermatitis, allergic rhinitis or food allergy. It is well acknowledged that genetic and environmental factors contribute to development of asthma. Research has been conducted about different environmental factors and their protective as well as predisposing effects. These studies focus mainly on prenatal period along with early years of life. Understanding the effects of environmental factors could possibly help us prevent several childhood-onset asthma cases. Aim: to review current data on the effect of environmental factors on childhood asthma. Methods: A database search on PubMed was carried out to summarize the effects of antibiotic usage, exposure to outdoor air pollution as well as farming environment and greenery on the incidence of childhood asthma. Studies published in English between 2017-2023 were selected. In addition, one older study from 2006 was included. All studies focused on children or included a child population (ages 0 to 18 years) Results: Altogether 16 original studies and two meta-analyses were included. Meta- analyses were used to support the results. Exposure to antibiotics during pregnancy and early years of life was associated with increased risk of childhood asthma. Exposure to outdoor air pollution during early life resulted in higher risk of developing childhood asthma. Living in rural area and being exposed to farming environment was associated with lower risk of asthma, although when viewing specifically effects of greenery, the results remained inconsistent. Conclusions: Based on these studies, minimizing the use of unnecessary antibiotics during early life may have protective effect on childhood asthma. In addition, by focusing on sustainability especially when it comes to traffic, the incidence of asthma could be decreased. Being exposed to farming environment seems to play a protective role, although a single study reported that farming environment didn’t seem to have protective effect on the long run, as the exposure increased the odds of later diagnosed asthma. When it comes to exposure to greenery, results remained conflicting and thus need further research. Key words: asthma, antibiotics, outdoor air pollution, rural, farming, greenery